Sofoklejeva Antigona na slovenskih poklicnih odrih - Kocijančič, Matic (Amfiteater (Ljubljana), 2022)
Sophocles’s Antigone has a rich and unique history of being performed on Slovenian professional stages for over a century. It began with the unsuccessful performance directed by Hinko Nučič in the Drama Ljubljana in 1912. It continued with Fran Lipah’s popular production in the same theatre on the eve of World War II. After the war, the Celje City Theatre took the lead in staging the tragedy; in fact, it was the only Slovenian professional theatre to stage it, first in 1956 (dir. Herbert Grün), then in 1973 (dir. Franci Križaj), and most recently in 2011 (dir. Anđelka Nikolić). The main reason for the odd absence of Sophocles’s Antigone on other Slovenian professional stages was probably the extraordinary popularity of Smole’s play by the same title, which was staged no less than eight times over this period. In addition, Sophocles was also ousted by the (rarer) staging of other modern Antigones (Dušan Jovanović, Miro Gavran, Janusz Głowacki). However, the last decade has seen revived interest in Sophocles’s version (and, at the same time, declining interest in staging Smole, which confirms our speculation that they compete for a place in the programme). Following the critically well-received production directed by A. Nikolić, the year 2013 was the first to see two productions, one in the Ljubljana City Theatre (play reading, dir. Ira Ratej) and the other in the Ljubljana Puppet Theatre (dir. Marko Čeh). Lastly, in 2017, Antigone also made a striking return to SNT Drama Ljubljana (dir. Eduard Miler). The article gives an overview of all these productions and evaluates them by drawing on their reception by contemporary critics and later theatre historians.
Keywords: Antigona; Antigone; Celje City Theatre; gledališka kritika; Ljubljana City Theatre; Ljubljana Puppet Theatre; Lutkovno gledališče ljubljansko; Mestno gledališče ljubljansko; performance concepts; SLG Celje; Slovenian theatre; slovensko gledališče; SNG Drama Ljubljana; SNT Drama Ljubljana; Sophocles; theatre criticism; uprizoritveni koncept